HEALTH CARE LICENSING (Study on Implementation Services Practice License and Work Permit Health Workers in the District Health Office of East Kutai Based on Local Regulation No. 45 Year 2010 on Main Duties and Functions (TOR) and Job Description Structura - Sujito, Hadi Ernata; Ventura NGW, Dr. Bona; Jatmikowati, Dr. Sri Hartini (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Implementation Services licensing on Health Office is the government effort to meet the basic needsand civil rights of every citizen in the goods, services and administrative services provided by thedelivery of public services. Reality shows that the condition of public services is still faced with a systemof government that has not been effective and effesien and quality of human resources is notadequate apparatus. It is seen from the number of complaints and complaints from the public, bothdirectly and through the mass media. Based on the description of the problems, the writer interestedin conducting research on: Licensing Services Health Workers in the District Health Office of East KutaiTo describe and analyze the advantages and barriers to implementation of License Practice (SIP) andWork Permit (SIK) Medicals. The research aimed to describe and analyze the Policy ImplementationServices, the service model, as well as the advantages and barriers to SIP and SIK licensing serviceprovided to the community. The results showed; No differentiation in the service of SIP servicemechanisms and Work Permit (SIK) at the District Health Office of East Kutai, the design of the modellicensing service designed to provide fast service, cheap and quality. The advantages and barriers toservices is affected by communication, resources, disposition, bureaucratic structure and delegationof authority.